DEVELOPING STUDENTS’ READING ACHIEVEMENT BY USING RECIPROCAL TEACHING - Ratna Nery (Language and Education Journal, 2016)
Reading is one of the most important skills to develop knowledge besides listening, speaking, and writing skills. It provides access the information due to the fact that it can give valuable knowledge to the readers who want to find the information. Ideas, opinion, or information can be gotten from how much the students read the books. Therefore the main purpose of this study was to prove whether or not the students who were taught reading by using reciprocal teaching had significantly different achievement than that of those who were not. The samples were the ninth grade students at State Junior High School 1 of Sirah Pulau Padang. The data obtained were taken by using a written test in the form of multiple choices. The data were analyzed by using t-test and all the computational procedures were run by using Statistical Package Social Science (SPSS). The result of independent samples t-test showed that t-obtained (4.352) was higher than the pvalue (.000) of ttable (1.9990). It means that there was a significant difference in reading achievement between the students who were taught by using reciprocal teaching and that of those who were not. The students who were taught by using reciprocal teaching could develop their reading achievement after experiencing with the classroom activities